"Fenomena Close Friends di Second Account Instagram: Manajemen Privasi pada Mahasiswa Laki-laki dan Perempuan": Fenomena Close Friends di Second Account Instagram: Manajemen Privasi pada Mahasiswa Laki-laki dan Perempuan - Amirah Farah Fahimah; Azizun Kurnia Illahi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study aims to explore private disclosures and privacy management among male and female university students who use the "Close Friends" feature on their secondary Instagram accounts. The research applies Communication Privacy Management (CPM) theory to analyze how individuals establish boundary rules and manage private disclosures when sharing both public and private information on social media. This study employs a descriptive qualitative approach, with data collected through in-depth interviews involving six university students who use the "Close Friends" feature on their secondary accounts. This study identifies differences in privacy management between male and female university students. Although both groups exhibit similar private disclosure patterns, male students tend to exercise greater caution when managing their privacy on Instagram. This study identifies differences in privacy management between male and female university students. Although both groups exhibit similar private disclosure patterns, male students tend to exercise greater caution when managing their privacy on Instagram. Additionally, the study finds that users of the Close Friends feature on secondary accounts manage their private information by establishing privacy rules according to their preferences as information owners. They coordinate private disclosures on social media through boundary linkages, boundary ownership, and boundary permeability, implementing thick boundaries. Some users of the Close Friends feature on their secondary accounts have experienced instances where friends on their close friends list shared private information they had disclosed. This led to privacy turbulence, prompting them to modify and refine the rules they had previously established